Review of Digital Marketing & Business Sustainability of E-Commerce During Pandemic Covid-19 In Indonesia - Santoso, Rudi (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2020)
This study examines the strategies used by MSMEs in order to survive and grow back during the Covid19 pandemic. The research object was 37 thousand MSME actors who experienced the direct impact of the pandemic. The method used is literature study. This research reveals that during a pandemic, consumers almost forget their brand, so communication through digital advertising will increase brand awareness again. Digital behavior encourages the expansion of online consumers, no longer to the millennial generation. Several MSMEs have gone bankrupt. But not a few who finally got up and then grew. MSMEs change production operations by reducing the amount of production and at the same time making innovations to increase competitiveness. On the other hand, the massive use of digital marketing has been carried out to increase customer awareness. Marketplace as a manifestation of e-commerce is used as an innovation or change in sales methods. Keywords: E-commerce, SMEs, Digital Marketing, Sustainability Business JEL: L60; L81; M31